2011
DOI: 10.1007/s11434-011-4568-y
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid and ethylene signaling pathways are involved in production of rice trypsin proteinase inhibitors induced by the leaf folder Cnaphalocrocis medinalis (Guenée)

Abstract: The roles of signaling pathways in the production of trypsin proteinase inhibitors (TrypPIs) in rice infested by the leaf folder (LF) Cnaphalocrocis medinalis were studied. Infestation by LF increased TrypPI levels in the leaves of rice plants at the tillering, booting and flowering stages but decreased TrypPI levels at the ripening stage; TrypPI levels in rice stems did not increase at any developmental stage. Infestation by LF at the tillering stage systemically increased TrypPI levels in leaves but not in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In our experiment, TI activity was found to increase in all the treated samples with respect to the control. A similar induced response was reported in rice (Casaretto et al 2004;Wang et al 2011). In addition amylase inhibitors, which act as an inhibitor of larval midgut amylase (Kluh et al 2005) accumulates due to foliar treatment with exogenous jasmonic acid was observed, previously (Délano-Frier et al 2004).…”
Section: Defense Enzyme Activities Upon H Armigera Infestationsupporting
confidence: 79%
“…In our experiment, TI activity was found to increase in all the treated samples with respect to the control. A similar induced response was reported in rice (Casaretto et al 2004;Wang et al 2011). In addition amylase inhibitors, which act as an inhibitor of larval midgut amylase (Kluh et al 2005) accumulates due to foliar treatment with exogenous jasmonic acid was observed, previously (Délano-Frier et al 2004).…”
Section: Defense Enzyme Activities Upon H Armigera Infestationsupporting
confidence: 79%
“…Studies of the regulation of these volatile compounds in plants show that their expression is often triggered by specific elicitors of herbivores that activate signaling pathways and genes related to plant defense . Rice plants that suffered herbivory from the rice leaffolder had increased levels of endogenous SA, and increased SA led to induced production of trypsin proteinase inhibitors . Zhao et al ., in contrast, did not find increases in SA levels in plants subjected to herbivory by S. frugiperda , but emission of methyl salicylate was higher in plants with S. frugiperda injury.…”
Section: Discussionmentioning
confidence: 91%
“…TrypPIs and HIPVs are important direct and indirect defense chemicals in rice against herbivores, and their production is regulated by JA, SA and ET signaling pathways (Zhou et al , Lu et al , Qi et al , Wang et al ). Therefore, we investigated if OsNPR1 modulates the production of TrypPIs and HIPVs.…”
Section: Resultsmentioning
confidence: 99%
“…Both JA and ET pathways have been reported to play an important role in mediating herbivore‐induced rice defense responses, including a positive regulation for the production of TrypPIs and HIPVs (Zhou et al , Lu et al , Lu et al , Qi et al , Wang et al ). Furthermore, in rice, TrypPIs have been reported to influence the performance of SSB (Zhou et al ), and HIPVs protect plants from attack by herbivores by attracting the natural enemies of the herbivores (Lou et al, , , Qi et al ).…”
Section: Discussionmentioning
confidence: 99%